Comparison of mechanical analyses and tongue pressure analyses during squeezing and swallowing of gels. (February 2015) - Hori, Kazuhiro; Hayashi, Hirokazu; Yokoyama, Sumiko; Ono, Takahiro; Ishihara, Sayaka; Magara, Jin; Taniguchi, Hiroshige; Funami, Takahiro; Maeda, Yoshinobu; Inoue, Makoto
Abstract: Dysphagic patients are fed soft meals made of gels and process them by squeezing the food with the tongue, which reduces food size. Although the gels are designed based on rheological analyses, the impact of the initial gel texture on tongue kinetics is not known. This study investigated the effect of gel consistency on tongue pressure during squeezing and swallowing and compared results of the mechanical analyses. Fifteen healthy young subjects participated in this study. Tongue pressure during squeezing and swallowing was measured by a sensor sheet with five measuring points. Five ml of water and six gel samples prepared using two gelling agents at three concentrations each were used as test materials. Subjects were instructed not to chew the food but to squeeze it using their tongue. The shape of the tongue pressure waveform during the initial squeeze was similar to the stress–time curve using a texture analyzer. However, the sequential order of tongue pressure during squeezing and swallowing was different. Tongue pressure during the initial squeeze was affected by gel consistency. The amplitude of tongue pressure during swallowing increased as gel consistency increased, but the duration of pressure was not affected. The slopes of tongue pressure generation were not affected by gel consistency, although the mechanical measurements showed increases in these slopes with increasing gel consistency. These results suggest that findings regarding characteristics of tongue movement during squeezing and textural properties of gels might be useful for food design and clarification of oral physiology. Graphical abstract: Highlights: The shape of tongue pressure waveform of initial squeeze was similar to the stress–time curve. The sequences of tongue pressure onset during squeeze and swallow were different. The amplitude of tongue pressure during squeezing was affected by gel consistency. The slopes of tongue pressure during squeezing were not affected by gel consistency.